2021
DOI: 10.1111/1346-8138.16039
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of tacrolimus ointment combined with dupilumab for patients with atopic dermatitis in real‐world clinical practice

Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease affecting people of all age groups worldwide. To our knowledge, there are currently no studies estimating the effectiveness of tacrolimus ointment and dupilumab as a combination therapy for AD. Thus, here we describe the effectiveness and safety of tacrolimus ointment in combination with dupilumab for facial rashes in patients with AD. Overall, we included 109 patients who newly received dupilumab from April 2018 to July 2020 in the Dermatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This fact supports the hypothesis that DRFE and pre‐existing facial AD have different pathomechanisms and that tacrolimus ointment might be a suitable option for the treatment of DRFE. While our observation is based on a single case, a previous study demonstrated combined effectiveness of tacrolimus ointment and dupilumab in clinical practice 2 . Malassezia hypersensitivity has been proposed to explain the pathomechanism of DRFE as well as that of AD, especially of the head and neck 2 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This fact supports the hypothesis that DRFE and pre‐existing facial AD have different pathomechanisms and that tacrolimus ointment might be a suitable option for the treatment of DRFE. While our observation is based on a single case, a previous study demonstrated combined effectiveness of tacrolimus ointment and dupilumab in clinical practice 2 . Malassezia hypersensitivity has been proposed to explain the pathomechanism of DRFE as well as that of AD, especially of the head and neck 2 .…”
Section: Discussionmentioning
confidence: 91%
“…While our observation is based on a single case, a previous study demonstrated combined effectiveness of tacrolimus ointment and dupilumab in clinical practice. 2 Malassezia hypersensitivity has been proposed to explain the pathomechanism of DRFE as well as that of AD, especially of the head and neck. 2 Actually, our patient's serum Malasseziaspecific IgE level was high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations